2013
DOI: 10.1515/znc-2013-1-206
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death of Rice Roots under Salt Stress May Be Mediated by Cyanide-Resistant Respiration

Abstract: Treatment with solutions containing high concentrations of NaCl (200 or 300 mM) induced cell death in rice (Oryza sativa L.) roots, as well as the application of exogenous hydrogen peroxide (H2O2). Moreover, the pretreatment with dimethylthiourea (DMTU), a scavenger of H2O2, partially alleviated the root cell death induced by 200 mM NaCl. These observations suggest that the cell death of rice roots under high salt stress is linked to H2O2 accumulation in vivo. NaCl stress increased the level of cyanide-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Corroborating these findings, AOX expression variation was also observed in Vigna unguiculata cultivars, contrasting in salt/drought stress tolerance [8]. In rice, generally, AOX1a and AOX1d are the stressresponsive genes (9,12,13,14,15,16,17,18). However, regarding the present experiment (seedling stage under 300 mM NaCl for 24 h) the higher AOX expression in the tolerant genotype was due to AOX1a (Figure 2D).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Corroborating these findings, AOX expression variation was also observed in Vigna unguiculata cultivars, contrasting in salt/drought stress tolerance [8]. In rice, generally, AOX1a and AOX1d are the stressresponsive genes (9,12,13,14,15,16,17,18). However, regarding the present experiment (seedling stage under 300 mM NaCl for 24 h) the higher AOX expression in the tolerant genotype was due to AOX1a (Figure 2D).…”
Section: Discussionsupporting
confidence: 75%
“…However, in monocots, the AOX2 subfamily is restricted only to some species of the Alismatales order [10], while most studies show that monocots have four or five AOX1 genes [9]. In rice, four AOX1 genes (AOX1a, 1c, 1d and 1e) have been found [9,11]; AOX1a and/or AOX1b (renamed to AOX1d) in [9] were induced by different stress conditions such as chilling, drought and high salt, while AOX1c was stably detected, and AOX1e was barely expressed in germinating seeds [9,[12][13][14][15][16][17][18]. In stress conditions, AOX relaxes the highly coupled and tensed electron transport process by driving electrons from quinol to oxygen, thereby alleviating tensed conditions and reducing ROS production [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the roots and leaves of rice seedlings, the AOX1a and AOX1b genes were induced by chilling, drought, and high salt, whereas the AOX1c gene was not responsive to these stresses [36,37]. Studies in rice seedlings further showed that the AOX1b gene exhibited a similar expression profile to AOX1a under chilling, drought, and high salt, but the transcript abundance of AOX1b was relatively lower [36,38]. These observations indicated that there are qualitatively and quantitatively different expression patterns among different AOX genes under abiotic stresses.…”
Section: Expression Of Aox Genes Under Abiotic Stressesmentioning
confidence: 99%
“…Lower root viability in turfgrass genotypes under drought stress corresponded to greater oxidative damage indicated by greater malondialdehyde content or lipid peroxidation. Greater oxidative damage in root cells under abiotic stresses has been associated with higher levels of cell death (Feng et al, 2013). Lokhande, Nikam, and Penna (2010) also reported that drought resulted greater oxidative damage, in terms of lipid peroxidation, than salt stress in Sesuvium portulacastrum L. under iso-osmotic salt and drought stresses.…”
Section: Discussionmentioning
confidence: 99%